Advances in Understanding of the Application of Unit Operations in Metallurgy of Rare Earth Elements - Srecko Stopic; Bernd Friedrich (Metals, 2021)
Unit operations (UO) are mostly used in non-ferrous extractive metallurgy (NFEM) and usually separated into three categories: (1) hydrometallurgy (leaching under atmospheric and high pressure conditions, mixing of solution with gas and mechanical parts, neutralization of solution, precipitation and cementation of metals from solution aiming purification, and compound productions during crystallization), (2) pyrometallurgy (roasting, smelting, refining), and (3) electrometallurgy (aqueous electrolysis and molten salt electrolysis). The high demand for critical metals, such as rare earth elements (REE), indium, scandium, and gallium raises the need for an advance in understanding of the UO in NFEM. The aimed metal is first transferred from ores and concentrates to a solution using a selective dissolution (leaching or dry digestion) under an atmospheric pressure below 1 bar at 100 °C in an agitating glass reactor and under a high pressure (40–50 bar) at high temperatures (below 270 °C) in an autoclave and tubular reactor. The purification of the obtained solution was performed using neutralization agents such as sodium hydroxide and calcium carbonate or more selective precipitation agents such as sodium carbonate and oxalic acid. The separation of metals is possible using liquid (water solution)/liquid (organic phase) extraction (solvent extraction (SX) in mixer-settler) and solid-liquid filtration in chamber filter-press under pressure until 5 bar. Crystallization is the process by which a metallic compound is converted from a liquid into a crystalline state via a supersaturated solution. The final step is metal production using different methods (aqueous electrolysis for basic metals such as copper, zinc, silver, and molten salt electrolysis for REE and aluminum). Advanced processes, such as ultrasonic spray pyrolysis, microwave assisted leaching, and can be combined with reduction processes in order to produce metallic powders. Some preparation for the leaching process is performed via a roasting process in a rotary furnace, where the sulfidic ore was first oxidized in an oxidic form which is a suitable for the metal transfer to water solution. UO in extractive metallurgy of REE can be successfully used not only for the metal wining from primary materials, but also for its recovery from secondary materials.